Clinical Characteristics of 31 Patients with Chest Pain Variant Asthma - Mao W; Gao Y; Sun W; Li J; Wang J; Wang Z; Zhang L; Huang K (Journal of Asthma and Allergy)
Wenping Mao,1 Yanli Gao,2 Wanlu Sun,1 Jie Li,1 Jing Wang,1 Zhaomei Wang,1 Liming Zhang,1 Kewu Huang1 1Department of Respiratory and Critical Care Medicine, Beijing Institute of Respiratory Medicine and Beijing Chao-Yang Hospital, Capital Medical University, Beijing, People’s Republic of China; 2Department of Radiology, Beijing Chao-Yang Hospital, Capital Medical University, Beijing, People’s Republic of ChinaCorrespondence: Kewu Huang, Department of Respiratory and Critical Care Medicine, Beijing Institute of Respiratory Medicine and Beijing Chao-Yang Hospital, Capital Medical University, Beijing, People’s Republic of China, Tel +86-010-85231167, Email kewuhuang@126.comPurpose: Asthma is a major public health challenge in China. Although chest pain variant asthma (CPVA) is not common in clinical practice, there are still a few people who only or mainly manifest as chest pain. Here, we aim to introduce the characteristics of their symptoms, lung function and chest imaging features to arouse the attention of physicians to know better of the disease.Patients and Methods: We retrospectively analyzed thirty-one patients who had been diagnosed with CPVA based on clinical data and positive bronchial provocation tests (BPTs).Results: The mean age of all enrolled patients was forty-seven years, and females accounted for 64.5%. Main features of chest pain manifested as dull pain and mild pain with unfixed location, and several patients were presented with distending pain, pinprick pain, chest pain related to breathing, chest pain position-related and chest pain like angina pectoris. The median duration of their chest pain was four months, and 77.4% of the patients did not find any trigger. Among the 31 patients, 10 were with normal lung function, 14 were with mild obstructive ventilation dysfunction, 6 were with small airway dysfunction and 1 was with mild restrictive ventilation dysfunction. The predicted values of forced expiratory volume in 1 s (FEV1) were greater than 80% in 29 out of 31 patients, and the values of other two patients were 74% and 79%, respectively. Additionally, 35.5% of the patients meanwhile had allergic rhinitis, and 64.5% of the patients exhibited type 2 inflammation. Among the 31 patients, 22 (71.0%) showed abnormalities on inspiratory computed tomography (CT) scans, including bronchiolar (38.7%), bronchial (25.8%) or pulmonary parenchyma abnormalities (32.3%). Only 7 patients (22.6%) had normal inspiratory CT scans.Conclusion: CPVA is relatively rare in clinical practice. Understanding its manifestations, lung function, chest CT features and comorbidities is helpful for diagnosis and evaluation of patients with such symptoms.Keywords: chest pain, atypical asthma, bronchial provocation test, chest computed tomography